A Peru that is born when life ends: Funeral practices at the Nueva Esperanza Cemetery - Aronés Pariona, Melcy Victoria (2019)
The city of Lima, at the beginning of the decade of the fifties, faced different cultural and social changes, due to the migrations that took place in the country. From that moment, Lima began to emerge as a multicultural city that was forging a new identity product of the mixture of diverse traditions and customs of the people. One way in which these cultural manifestations are expressed is in funeral practices.